Building energy codes and their impact on greenhouse gas emissions in the United States - Pint, Alexander Steven (Kansas State University, 2015)
The purpose of this study is to identify and explore relationships between the building industry, building energy usage, and how both the industry and the energy usage correspond to greenhouse gas (GHG) emissions in the United States. Building energy codes seek to reduce energy usage and, subsequently, GHG emissions. This study specifically seeks to determine the impact that most current U.S. building energy codes could have on national GHG emissions if widespread adoption and enforcement of those codes were a reality. The report initially presents necessary background information about GHG emissions is first discussed. This establishes the current state of global GHG emissions, the position of the U.S. within the global scale, and what portion of the contribution can be attributed to the building industry. The report also describes the current issues and benefits of building energy codes. An overview of building energy codes evaluation is included, with explanation of the energy analysis used to determine the effectiveness of new building energy codes. In order to determine how to improve the building energy code system, an analysis of ANSI/ASHRAE/IES Standard 90.1-2013 (equivalent to 2015 IECC, the most recent standard available) is conducted to reveal unrealized GHG emission reductions that are expected with adoption and compliance to the newest code. Standard 90.1-2013 is analyzed due to the national popularity of the code relative to other building energy codes. This analysis includes compilation of energy usage intensity, square footage, and current code adoption data throughout the United States. Results showed that the excess GHG emission savings from enhanced adoption and compliance was not significant on a national scale. However, in terms of GHG emissions currently saved by building energy codes, the extra savings becomes more significant, proving that increased adoption and compliance is a worthwhile pursuit. Recommendations are then made for how to increase adoption and compliance. This information will give policymakers improved understanding of the current state of the industry when crafting laws regarding GHG emissions and building energy codes. Furthermore, findings from this study could benefit specific states that are attempting to lower GHG emissions.
Keywords: Building Energy Codes; Greenhouse Gas Emissions; ANSI/ASHRAE/IES Standard 90.1-2013; Architectural engineering (0462); Engineering (0537)